Efecto de la aplicación de silicio (SiO2) en el control de mildiu velloso (Pseudoperonospora cubensis) en cultivo de pepino (Cucumis sativus) - Ramírez Orobio, Jenniffer Josimara (2021)
Downy mildew is a disease caused by the fungus pseudoperonospora cubensis, responsible for large losses in cucumber crop production. The present research was carried out with the objective of evaluating the effect of silicon (SiO2) application in the control of downy mildew (Pseudoperonospora cubensis) in cucumber (Cucumis sativus). The research was carried out at the Experimental Farm "La María" belonging to the State Technical University of Quevedo (UTEQ), located on the Quevedo-El Empalme road at km 7 in the Province of Los Ríos. The fertilizer applied was SILICAMAG SiO2 (32%), in different doses applied at 8, 23 and 40 days after planting. A completely randomized block design (CRBD) was used, with seven treatments and three replications per treatment. The variables evaluated were downy mildew disease severity in different treatments and leaves of different heights using a visual assessment scale and image processing. Yield per plant and a benefit/cost economic analysis were evaluated. To validate the image processing, a linear correlation with visual scale was used and the rest of the variables were subjected to analysis of variance (Tukey p<0.05) to determine statistical differences. The results obtained show a positive correlation (R2:0.98) of the Leaf Doctor program with the visual assessment. Downy mildew severity did not show differences among treatments, but the greatest affectation was on the lower leaves, with the highest percentage of affectation on the lower leaves. The treatment with the highest yield was T7 (Si: 540 kg/ha), which also had a 55% increase in yield compared to the control. Keywords: Leaf Doctor, Pseudoperonospora cubensis, cucumber, yield.